A STUDY ON THE RELATIONSHIP BETWEEN ORGANIZATIONAL SOCIALIZATION AND ORGANIZATIONAL SILENCE - Demir, Selçuk (Behçet ORAL, 2021)
In this study, it has been purposed of determining the connection between organizational socialization and organizational silence perception of teachers. The teachers working in Kırıkhan district, in Hatay province constitute the universe of this study. And, the sample of this study consists of 217 teachers in 30 schools which have been selected by lot. “Organizational Socialization Scale’’, which has been developed by Erdoğan and Sönmez (2019) has been utilized to identify the views of teachers in respect of socialization. This scale has 5 dimensions and 24 items. ‘’Organizational Silence Scale’’, which has been developed by Kahveci ve Demirtaş (2013) has been used to determine the teacher views about organizational silence levels. This scale consists of 5 dimensions and 18 items. Cronbach-Alpha Reliability Coefficients, which has been calculated according to these scales utilized in this research, has shown that scales are reliable. In the analysis of research data, by the help of SPSS programme, it has been utilized for correlation, simple and multiple regression analysis. At regression analysis results, it has been detected that the socialization perception of teachers is a significant predictor of organizational silence perception. And, it has been revealed at multiple regression analysis outcomes that the dimension of adaptation to goals and values of organizational socialization is a meaningful predictor of organizational silence, while other dimensions were not significant predictors of organizational silence.

Bu çalışmada; öğretmenlerin örgütsel sosyalleşme ile örgütsel sessizlik algıları arasındaki ilişkinin belirlenmesi amaçlanmaktadır. Hatay ilinin Kırıkhan ilçesinde görev yapan öğretmenler, bu çalışmanın evrenini oluşturmaktadır. Araştırmanın örneklemi ise çalışma evreninden kura ile belirlenen 30 okuldaki 217 öğretmenden oluşmaktadır. Öğretmenlerin sosyalleşmeye ilişkin görüşlerini belirlemek için Erdoğan ve Sönmez (2019) tarafından geliştirilen “Örgütsel Sosyalleşme Ölçeği” kullanılmıştır. Ölçek; beş boyuttan ve 24 maddeden meydana gelmektedir. Öğretmenlerin örgütsel sessizlik düzeylerine ilişkin görüşlerini saptamak için ise Kahveci ve Demirtaş (2013) tarafından geliştirilen “Örgütsel Sessizlik Ölçeği” kullanılmıştır. Bu ölçek, 5 boyuttan ve 18 maddeden meydana gelmektedir. Araştırmada yararlanılan bu ölçeklere ilişkin hesaplanan Cronbach-Alfa güvenirlik katsayıları, ölçeklerin güvenilir olduklarını göstermiştir. Araştırma verilerinin analizlerinde; SPSS programı yardımıyla korelasyon, basit ve çoklu regresyon analizlerinden yararlanılmıştır. Regresyon analizi sonucunda; öğretmenlerin sosyalleşme algısının, örgütsel sessizlik algısının anlamlı bir yordayıcısı olduğu tespit edilmiştir. Çoklu regresyon analizi sonucunda ise örgütsel sosyalleşmenin; amaç ve değerlere uyum boyutunun, örgütsel sessizliğin anlamlı bir yordayıcısı olduğu, diğer boyutlarının ise örgütsel sessizliğin anlamlı birer yordayıcısı olmadıkları açığa çıkarılmıştır.
ÖRGÜTSEL SOSYALLEŞME İLE ÖRGÜTSEL SESSİZLİK ARASINDAKİ İLİŞKİ ÜZERİNE BİR ÇALIŞMA
Keywords: Other Fields of Education; Alan Eğitimleri